ATF, Inc. : fasteners and family - Ward, John L., 1945- (SAGE Knowledge. Cases., 2017)
The ATF case is a succinct opportunity to explore the many special features of leadership succession for a family business. In 2009 the company was passing the baton to the oldest of three sons in the second-generation family business. ATF produced metal and plastic fasteners for, primarily, the automotive industry. ATF had grown into a company with more than $50 million in annual revenues. The company had grown in large part through alliances with other family businesses around the world. First-generation patriarch Don Surber had led the company since he acquired it in 1982. Don was known for his charismatic leadership style and his focus on driving value through a network approach.The case traces the career paths of all three sons and looks at the succession through the eyes of the oldest son, Jason Surber. The elements, constituents, and challenges of succession are evident. The fundamental insight is that business leadership succession is far more than just passing the business leadership baton. It also requires attention to the family, the board, the whole system of external stakeholders, and the future of ownership.The epilogue in this note covers the period from 2009 to 2012 by describing what Jason did to earn credibility, to incorporate his brothers, and to define his personal leadership philosophy and style. The epilogue thus provides students with an opportunity to consider and define their own personal philosophy of management leadership and their own style. They will see the art of melding styles from the past with their own for the future.